Development of a Holonomic Transmission Module for Service Robot - Fairuz Abdul Jalal, Muhammad; Chadaran, Dhiviandran; Salleh Mohamed Sahari, Khairul (International Journal of Engineering and Technology, 2019)
The paper presents the development of transmission module for service robot by utilizing the holonomic drive system. Thorough study was done on existing research and all the relevant technical information was reviewed. The analysis on existing transmission module design was made and all the mechanical improvement was made. All the problems were identified and proper solution made. New designs of parts and the development of control module were done. This includes replacement of critical parts such as mounting brackets and drawer for the housing of the transmission module developed. Important mechanical analysis such as motor selection, force analysis, and FEA was made. The final design is analyzed and modelled using commercial software. The control module of robot was designed and developed, involving usage of Arduino IDE, software for programming Arduino controller. Analysis on the transmission module made was to validate the module developed, including workability of the developed mechanical parts, and the omnidirectional drive system. The project was aimed to be the base of the service robot, therefore the robot was tested and the results obtained were discussed.Â Â